Koreografi Tari Gamaro di Sanggar Seni Sari Bunian di Kanagarian Andaleh Kecamatan Sungayang Kabupaten Tanah Datar - Ranti Arfira Nofeni; Darmawati Darmawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The purpose of this study is to reveal and describe the choreography of Gamaro Dance at Sari Bunian Art Studio in Kanagarian Andaleh, Sungayang District, Tanah Datar Regency. This type of research is quantitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews, and documentation. The steps of analyzing data are collecting data, describing the data and inferring the data. The results showed that this Gamaro dance has 3 parts, namely the beginning as the opening of the dance, the middle, and the end as the climax. In this Gamaro dance there are dance composition elements consisting of movement, floor design, group composition, upper design, dancers, music design, costumes and makeup and props. The movement worked on by the choreographer depicts the activities of residents who work as niro farmers. This dance work also looks very interesting with floor patterns and diverse group compositions so that the audience does not get bored in watching the performance and dancers who master strong movements and movements. The costumes used in the Gamaro dance are simple costumes. This Gamaro dance raised the theme of the activities of residents in Kanagarian Andaleh Baruh Bukik as niro farmers. The music that accompanies the dancer's movements uses a fast tempo until the end of the dance with drumming singing. The property used in Gamaro dance is niro tube or bamboo tube.